Influence of Financial Literacy, Risk Tolerance, Financial Efficacy on Investment Decisions and Financial Management Behavior - Firda Nisafera Ulfa; Supramono Supramono; Ardiani Ika Sulistyawati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The problem in this study lies in the development of financial literacy in the age range of 18-25 years which has continued to decrease by 3 times in a row since the SNLIK (National Survey of Financial Literacy and Inclusion) was conducted. This age range is included in the Z generation category. SNLIK was first conducted in 2013, and the survey is conducted every 3 years by the OJK (Financial Services Authority). From this phenomenon, it can be a reference that there are many Generation Z people who are afraid or fail or have not made an investment decision. This study aims to determine how understandable and effective financial literacy, risk tolerance, financial efficacy are in making investment decisions and financial management behavior.The population of this study is generation Z of Indonesia with birth ranges from 1996 to 2009. The sampling technique was purposive sampling with a total sampling of 200 respondents. The type of data used is primary data and secondary data. The data collection method used is through an online questionnaire (google form). The analysis technique used is SEM with Smart pls 3.0 software. The results showed that: financial literacy has an effect on financial management behavior, risk tolerance has no effect on financial management behavior, financial efficacy has had an effect on financial management behavior, financial literacy has had an effect on investment decisions, risk tolerance has had an effect on investment decisions, financial efficacy has no effect on decisions Investment and financial management behavior influence investment decisions.